The Influence of Financial Adequacy, Religiosity, Humanity and Institutions on Donating Behavior at LAZISMU Magelang City - Ariq Fikria Niagasi; Harjum Muharram (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The huge potential of zakat in Indonesia makes it an opportunity for zakat institutions in Indonesia to collect zakat funds from the public. Based on the 2020 Census data by the Central Statistics Agency, there are 270 20 million people in Indonesia. 70.72% are of productive age, which can be a potential muzakki zakat income, and 85% are Muslim. However, the income zakat collected in Indonesia is still relatively small. At the same time, the number of zakat institutions in Indonesia is enormous. This study uses quantitative methods, and the research data is obtained by distributing questionnaires to donors containing questions related to donors' behavior in giving donations to Lazismu, Magelang City. So it is found that the data that the donors who secure their contributions through Lazismu Magelang City are not because of the problem of whether or not their financial strength is sufficient or not to meet their daily needs but because of the high level of concern among others.